The Impact of Covid-19 On State-Religion Relations: A Study On Israel And Iran - (:unkn) unknown (ILEM, 2021)
Regulations, measures and restrictions implemented by state authorities on public events and mass gatherings due to fear, anxiety, and panic caused by COVID-19 pandemic have made religious field more open to state intervention since the global pandemic started and religious practices underwent radical changes. Governments' public health measures concerning the places of mass worship and religious gatherings to stop the spread of the pandemic and the reactions of religious groups against their orders and imposed restrictions emerged as a new dimension of the debates on state-religion and state-individual relations. In this regard, the main purpose of the study is to discuss the new global religious trends that emerged with the outbreak of COVID-19 pandemic, which reshapes state-religion relations through the regulations and measure for containing the virus, in light of the experiences in different regions and religious traditions, and to analyze the relationship between the religion and the state in the Middle East, specifically the cases of Israel and Iran as religious character is dominant and orthodox religious groups play a significant role within the social and political structure in both countries.
Keywords: COVID-19 Pandemic; Religious Trends; State-Religion Relationship; Israel; Iran; CATHOLICISM